DIAGNOSIS OF PNEUMONIA IN CHILDREN AND INDICATIONS FOR HOSPITALIZATION - Ibatova Шоира; Abdullaeva Мавжуда; Mamatkulova Дилрабо (International Journal of Scientific Pediatrics, 2024)
Among lower respiratory tract infections, pneumonia is one of the serious problems of childhood. According to foreign studies, the prevalence of community-acquired pneumonia is 34-40 cases per 1000 children per year. Purpose of the study: to determine the role of timely diagnosis and comprehensive treatment of pneumonia in an outpatient setting in the prognosis of acute pneumonia in children. Materials and methods: in 98 patients aged from 3 months to 3 years who applied to the family clinic No. 2 of Samarkand with acute respiratory diseases, patient complaints, anamnestic data, clinical symptoms were studied, the results of laboratory and instrumental research methods were analyzed and Based on them, recommendations have been developed for hospitalization of sick children with acute pneumonia. Results: the role of timely diagnosis and comprehensive treatment of pneumonia in an outpatient setting in the prognosis of acute pneumonia in children was determined. Conclusion. Timely diagnosis and comprehensive treatment of pneumonia in an outpatient setting significantly improves the prognosis of acute pneumonia in children.